Corporate efficiency in Europe - Hanousek, Jan; Kočenda, Evžen; Shamshur, Anastasiya (Journal of Corporate Finance, 2015)
Using a stochastic frontier model and a comprehensive dataset, we study factors that affect corporate efficiency in Europe. We find that (i) larger firms are less efficient than smaller firms, (ii) greater leverage contributes to corporate efficiency, and (iii) high competition is less conductive to efficiency than moderate or low competition. In terms of ownership, we find that (iv) efficiency increases when a majority owner must deal with minority shareholders and that (v) domestic majority owners improve efficiency more than foreign majority owners when no minority shareholders are present, but (vi) the opposite is true when minority shareholders hold a substantial fraction of the firm's equity. In the analysis, we distinguish between a pre-crisis period (2001–2008) and a post-crisis period (2009–2011), and find that our results are sensitive to the period of observation.